2012
DOI: 10.1016/j.chom.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Healthy Human Gut Microbiome: Current Concepts, Future Directions, and Clinical Applications

Abstract: Indigenous microbiota are an essential component in the modern concept of human health, but the composition and functional characteristics of a healthy microbiome remain to be precisely defined. Patterns of microbial colonization associated with disease states have been documented, but the health-associated microbial patterns and their functional characteristics are less clear. A healthy microbiome, considered in the context of body habitat or body site, could be described in terms of ecologic stability (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
526
0
30

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 668 publications
(561 citation statements)
references
References 81 publications
5
526
0
30
Order By: Relevance
“…Os tecidos imunes presentes no trato gastrointestinal constituem a maior e mais complexa fracção do sistema imunológico humano 16 . No intestino, a microbiota tem a função de "educar" o sistema imunológico e prevenir infecções patogênicas, e seu benefício se estende por outros órgãos, inclusive os pulmões 17 .…”
Section: Imunidadeunclassified
See 2 more Smart Citations
“…Os tecidos imunes presentes no trato gastrointestinal constituem a maior e mais complexa fracção do sistema imunológico humano 16 . No intestino, a microbiota tem a função de "educar" o sistema imunológico e prevenir infecções patogênicas, e seu benefício se estende por outros órgãos, inclusive os pulmões 17 .…”
Section: Imunidadeunclassified
“…A microbiota humano estabelece no início da vida (no parto) sofrendo alterações desde o nascimento (idade gestacional, tipo de parto -parto vaginal ou parto cesariano) e ao longo da vida, influenciado por fatores como idade, alimentação, localização geográfica, o consumo de suplementos e fatores ambientais 16,29,30 . Além das doenças inflamatórias e autoimunes, existem outras doenças crônicas que podem ser afetadas pela comunidade microbiana do intestino.…”
Section: Fatores Determinantes Da Microbiotaunclassified
See 1 more Smart Citation
“…A study on the consumption of a probiotic yogurt revealed the changes in expression of microbiome-encoded enzymes (related to carbohydrate metabolism), but no impact was found on microbial populations in faeces [59]. Several possibilities for the use of probiotics in dysbiosis conditions are there that may include use of a modified consortium or genetically engineered bacteria for targeted, enhanced benefits [59,60].…”
Section: Human Innate Gut Microbiota and Its Variationmentioning
confidence: 99%
“…However, it is still not clear to the researchers if prebiotic involvement promotes constancy in the population or results only in temporary shifts of population that are beneficial [62]. Correspond a prebiotic with a probiotic (forming a synbiotic) may be a fresh approach to make dietary-induced changes in the gut microbiota [60].…”
Section: Human Innate Gut Microbiota and Its Variationmentioning
confidence: 99%